LINGU(AGEM)ÍSTICA E A CIÊNCIA COGNITIVA: BREVE REVISÃO - Souza, Sueder (LINKSCIENCEPLACE, 2026)
We seek to present here the ways that the area of Linguistics come to get your statute as cognitive science. Thus, in seeking to understand the knowledge that are represented in the mind, through intersection with other areas of knowledge, and especially to the areas of cognitive bias, we intend to propose a discussion about the diversity of working areas with linguistics; of its status as cognitive science; the approach to neuroscience; and areas of research working with language.